2007
DOI: 10.1128/iai.01667-06
|View full text |Cite
|
Sign up to set email alerts
|

A Novel ChimericPlasmodium vivaxCircumsporozoite Protein Induces Biologically Functional Antibodies That Recognize both VK210 and VK247 Sporozoites

Abstract: A successful vaccine against Plasmodium vivax malaria would significantly improve the health and quality of the lives of more than 1 billion people around the world. A subunit vaccine is the only option in the absence of long-term culture of P. vivax parasites. The circumsporozoite protein that covers the surface of Plasmodium sporozoites is one of the best-studied malarial antigens and the most promising vaccine in clinical trials. We report here the development of a novel "immunologically optimal" recombinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 53 publications
4
73
1
1
Order By: Relevance
“…In addition to these quantitative effects on the antibody response, VMP001-ICMV immunization also changed the qualitative nature of the antibody response, promoting a more balanced Th1/Th2 response (both in terms of T-cell cytokine production and antibody isotypes) and broadening the antibody targets within VMP001, including epitopes implicated in protection against Plasmodium (5). We previously reported that immunization with Freund's adjuvant, a very strong but toxic adjuvant for small-animal experimental immunization, could elicit responses against multiple epitopes within VMP001 (5). Here we have made the important advance of achieving broad antibody responses using clinically relevant adjuvant materials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to these quantitative effects on the antibody response, VMP001-ICMV immunization also changed the qualitative nature of the antibody response, promoting a more balanced Th1/Th2 response (both in terms of T-cell cytokine production and antibody isotypes) and broadening the antibody targets within VMP001, including epitopes implicated in protection against Plasmodium (5). We previously reported that immunization with Freund's adjuvant, a very strong but toxic adjuvant for small-animal experimental immunization, could elicit responses against multiple epitopes within VMP001 (5). Here we have made the important advance of achieving broad antibody responses using clinically relevant adjuvant materials.…”
Section: Discussionmentioning
confidence: 99%
“…VMP001 was prepared as previously described (5,6). Synthesis of ICMVs was performed as described previously with slight modifications (10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 A leading PvCSP approach involves a chimeric circumsporozoite construct, expressed in E. coli, that contains major CS repeats from the two major alleles (VK210 and VK247). 46 Antibodies from immunized mice recognized both VK210 and VK247 sporozoites and cause agglutination of live sporozoites, an in vitro surrogate of sporozoite infectivity. 46 A leading PvRII antigen, also produced in E. coli, has been demonstrated to elicit relevant antibodies, using an in vitro binding inhibition assay, following immunization of Rhesus macaques with PvRII formulated with when administered with either Alhydrogel, Montanide ISA720 or AS02 adjuvant.…”
Section: Plasmodium Vivax Vaccinesmentioning
confidence: 99%
“…46 Antibodies from immunized mice recognized both VK210 and VK247 sporozoites and cause agglutination of live sporozoites, an in vitro surrogate of sporozoite infectivity. 46 A leading PvRII antigen, also produced in E. coli, has been demonstrated to elicit relevant antibodies, using an in vitro binding inhibition assay, following immunization of Rhesus macaques with PvRII formulated with when administered with either Alhydrogel, Montanide ISA720 or AS02 adjuvant. 47 Looking ahead, a multi-antigen, multistage approach, which would necessitate the two antigens, CSP and PvRII, being combined and formulated with a common adjuvant, may offer the best opportunity for success.…”
Section: Plasmodium Vivax Vaccinesmentioning
confidence: 99%